Adaptor protein CRK induces epithelial–mesenchymal transition and metastasis of bladder cancer cells through HGF/c‐Met feedback loop. Issue 6 (22nd April 2015) - Matsumoto, Ryuji; Tsuda, Masumi; Wang, Lei; Maishi, Nako; Abe, Takashige; Kimura, Taichi; Tanino, Mishie; Nishihara, Hiroshi; Hida, Kyoko; Ohba, Yusuke; Shinohara, Nobuo; Nonomura, Katsuya; et al.
<x xml:space="preserve">Abstract</x> We have previously reported that an adaptor protein CRK, including CRK‐I and CRK‐II, plays essential roles in the malignant potential of various aggressive human cancers, suggesting the validity of targeting CRK in molecular targeted therapy of a wide range of cancers. Nevertheless, the role of CRK in human bladder cancer with marked invasion, characterized by distant metastasis and poor prognosis, remains obscure. In the present study, immunohistochemistry indicated a striking enhancement of CRK‐I/‐II, but not CRK‐like, in human bladder cancer tissues compared to normal urothelium. We established CRK‐knockdown bladder cancer cells using 5637 and UM‐UC‐3, which showed a significant decline in cell migration, invasion, and proliferation. It is noteworthy that an elimination of CRK conferred suppressed phosphorylation of c‐Met and the downstream scaffold protein Gab1 in a hepatocyte growth factor‐dependent and ‐independent manner. In epithelial–mesenchymal transition‐related molecules, E‐cadherin was upregulated by CRK elimination, whereas N‐cadherin, vimentin, and Zeb1 were downregulated. A similar effect was observed following treatment with c‐Met inhibitor SU11274. Depletion of CRK significantly decreased cell proliferation of 5637 and UM‐UC‐3, consistent with reduced activity of ERK. An orthotopic xenograft model with bioluminescent imaging revealed that CRK knockdown significantly attenuated not only tumor volume but also the number of circulating tumor cells, resulted in a complete abrogation of metastasis. Taken together, this evidence uncovered essential roles of CRK in invasive bladder cancer through the hepatocyte growth factor/c‐Met/CRK feedback loop for epithelial–mesenchymal transition induction. Thus, CRK might be a potent molecular target in bladder cancer, particularly for preventing metastasis, leading to the resolution of clinically longstanding critical issues.